2022
DOI: 10.1002/ddr.21941
|View full text |Cite
|
Sign up to set email alerts
|

Xanthatin inhibits non‐small cell lung cancer proliferation by breaking the redox balance

Abstract: Lung cancer is the cancer with the highest mortality, and non-small cell lung cancer (NSCLC) accounts for more than 80%. Tumor cells often have high reactive oxygen species (ROS) and antioxidant capacity. Redox balance is very important for tumor. The decline of antioxidant capacity and excessive ROS will induce the death of tumor cells. Destroying the redox balance of tumor cells is a promising tumor treatment strategy. Xanthatin is an active sesquiterpene lactone isolated from Xanthium strumarium L. We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…In the following study, they found that xanthatin ( 1 ) could suppress DNA replication by triggering Chk1-mediated DNA damage [ 71 ]. In 2018, Fang et al, reported that xanthatin ( 1 ) could promote the oxidative stress-mediated apoptosis of HeLa cells via inhibiting thioredoxin reductase, which was supported by the research of Zhang et al, in 2021 [ 72 , 73 ]. In 2019, Yu et al, demonstrated that xanthatin could covalently bind to JAK and IKK kinases and inhibit the STAT3 and NF-κB signalling pathways to suppress the development of cancer and inflammatory diseases [ 74 ].…”
Section: The Biological Activity Of Xanthanolidesmentioning
confidence: 90%
“…In the following study, they found that xanthatin ( 1 ) could suppress DNA replication by triggering Chk1-mediated DNA damage [ 71 ]. In 2018, Fang et al, reported that xanthatin ( 1 ) could promote the oxidative stress-mediated apoptosis of HeLa cells via inhibiting thioredoxin reductase, which was supported by the research of Zhang et al, in 2021 [ 72 , 73 ]. In 2019, Yu et al, demonstrated that xanthatin could covalently bind to JAK and IKK kinases and inhibit the STAT3 and NF-κB signalling pathways to suppress the development of cancer and inflammatory diseases [ 74 ].…”
Section: The Biological Activity Of Xanthanolidesmentioning
confidence: 90%
“…For example, Verma et al found that isodeoxyelephantopin and deoxyelephantopin can inhibit the activation of NF-κB by inducing the production of ROS and inhibit the growth of breast cancer [ 55 ]. Xanthatin, a sesquiterpenoid derived from Xanthium strumarium L, may induce the elevation of ROS, mitochondrial injury, and apoptosis in non-small cell lung cancer (NSCLC) [ 56 ]. The ability of sesquiterpenes to induce ROS generation may stem from the fact that they both have α-methylene-γ-lactone and [ 57 ] a cyclopentenone ring-like structure (butenolide in scabertopin) ( Figure 1 A) [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-dose NAC inhalation therapy shows promise in rectifying the oxidant-antioxidant imbalance observed in lung tissue of IPF patients, thereby ameliorating fibrotic progression [ 180 ]. β-mercaptoethanol functions as a reducing agent that facilitates cysteine uptake for maintaining optimal GSH levels [ 181 , 182 ]. Studies have demonstrated that β-mercaptoethanol can inhibit the proliferation of human lung fibroblasts by modulating ferroptosis-related pathway [ 183 ].…”
Section: Strategies For Targeted Ferroptosis In Pfmentioning
confidence: 99%